2019
DOI: 10.15835/nbha47411712
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Response to Planting Patterns under Effect of Typical and Limited Irrigation Regime

Abstract: Decrease of width between cotton (Gossypium hirsutum L.) row spacing has been suggested as an agronomic practice that may increase the yield and reduce the cost production. Altering agronomic practices as row spacing system as well as irrigation regime can affect cotton growth parameters, yield components, and physical fiber properties. The object of this study is the assessment of interaction between row spacing cropping systems and irrigation regime and their effects on yield components. Yield, biomass, harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In this respect, Gebregergis et al (2020) reported that sowing cotton with wide planting geometry (80 x25 cm) increased open bolls compared to narrow planting geometry (60 x 10 cm). Boll weight and seed index were increased by increasing furrow width (96 cm) in comparison with (50 and 75 cm) as reported by Darawsheh et al (2019).…”
Section: -Yield and Seed Qualitysupporting
confidence: 69%
“…In this respect, Gebregergis et al (2020) reported that sowing cotton with wide planting geometry (80 x25 cm) increased open bolls compared to narrow planting geometry (60 x 10 cm). Boll weight and seed index were increased by increasing furrow width (96 cm) in comparison with (50 and 75 cm) as reported by Darawsheh et al (2019).…”
Section: -Yield and Seed Qualitysupporting
confidence: 69%
“…According to our results, the leaf area index LAI, was affected significantly by irrigation treatment. This is explained by the fact that irrigation leads to an increase in biomass production [5]. In addition, an increase in the irrigation dose led to an increase in LAI, up to 100 days after plant emergence, after which fruit production is promoted [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cotton species, G. hirsutum is the most widely cultivated species worldwide 1 , 2 . Annual fiber production and plantation area of cotton vary from year to year but the most recent data showed that fiber production was about 26 million tons and planted area was about 35 million hectares 3 , 4 . Among the cotton-producing countries, India, the People’s Republic of China, the United States of America (USA), Pakistan, Uzbekistan and Brazil are the leading countries.…”
Section: Introductionmentioning
confidence: 99%
“…Interspecific crossing for crop improvement experiments within and between major species, including cotton produced limited success 2 , 5 . In traditional agriculture of cotton, grafting, transplantation and pruning practices were not widely used 4 . However, these practices have been increasingly applied in some areas of China and with the need for more rotational cropping and transplanting of seedlings, it seems that there will be a wider application of these practices in cotton agriculture 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation